2010
DOI: 10.2188/jea.je20090121
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Factors Associated with Tinnitus: A Community-Based Study of Japanese Elders

Abstract: BackgroundThe prevalence of tinnitus is reported to be high in older Western populations, and several risk factors have been suggested. However, community-based evidence on prevalence is limited and, to our knowledge, there is no such information from older non-Western populations. The purpose of this study was to determine the prevalence and factors associated with tinnitus in community-dwelling Japanese elders.MethodsIn this community-based cross-sectional study, 1320 residents of Kurabuchi Town aged 65 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 32 publications
7
80
1
8
Order By: Relevance
“…We found no significant difference in tinnitus prevalence according to smoking status, confirming findings from most other studies [17,20,21,36]. Only a few surveys reported a higher prevalence of tinnitus in current than in never smokers [9,10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found no significant difference in tinnitus prevalence according to smoking status, confirming findings from most other studies [17,20,21,36]. Only a few surveys reported a higher prevalence of tinnitus in current than in never smokers [9,10].…”
Section: Discussionsupporting
confidence: 90%
“…Indeed a few studies showed that tinnitus and cardiovascular diseases share several risk factors [10,41], supporting the hypothesis that a healthy microvascular system in the inner ear [41], cochlear nerve [45] and central auditory system (which is responsible for tinnitus chronicization) [4] may reduce the risk of tinnitus. Other studies, however, did not find any relation between alcohol drinking and risk of tinnitus [17,20,21,36]. …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…3 The results of the study showed a prevalence of 10•1% among adults, with the tinnitus described as moderately annoying by 2•8% of respondents, severely annoying by 1•6%, and at a level that severely aff ected ability to lead a normal life by 0•5%. Results from studies in Egypt, 4 Japan, 5 and Nigeria, 6 indicate tinnitus prevalence is broadly similar in these countries to in Europe and the USA. The prevalence of troublesome tinnitus increases with age to 70 years; results of some studies show that it continues to increase thereafter, although others have shown it to diminish.…”
Section: Epidemiologymentioning
confidence: 88%
“…Precisamente, la dificultad para definir las características psicoacústicas de los acufenos, intensidad y frecuencia principalmente, permite comprender por qué los estudios de agregación familiar no han demostrado ninguna heredabilidad (16), y que no se haya podido establecer diferencias en la prevalencia de los acúfenos de acuerdo al origen étnico de la población (17)(18)(19).…”
Section: Genética De Los Acúfenosunclassified